Co-limitation by N and P Characterizes Phytoplankton Communities Across Nutrient Availability and Land Use - Bratt, A. R.; Finlay, J. C.; Welter, J. R.; Vculek, B. A.; Van Allen, R. E. (Ecosystems (New York), 2020)
Historically, freshwater lakes have been widely assumed to be singly limited by phosphorus (P) because the dominant paradigm assumes that nitrogen fixation (N₂ fixation) will compensate for any nitrogen (N) deficits. However, a growing body of evidence demonstrates that primary producer response to nutrient manipulation most frequently indicates co-limitation by N and P. Differences in N and P supply ratio have been shown to influence the identity and severity of nutrient limitation, but whether N and P concentration and the ratio of N to P concentrations can explain the frequency of co-limitation in aquatic primary producer assemblages remains unclear, especially in ecosystems subject to human perturbation that strongly increase nutrient availability. We determined how resource availability influences nutrient limitation by N and P of phytoplankton primary production across 12 lakes in Minnesota that vary in watershed land use and lake nutrient levels. We measured epilimnetic lake metabolism and indicators of N₂ fixation to evaluate their influence on nutrient limitation status of planktonic algal assemblages. Despite large differences in land use (agricultural, urban, and suburban) and water column N and P availability, planktonic algal response to nutrient manipulation was consistently characterized by co-limitation by N and P across years and months. Neither P availability (as concentrations of total and inorganic forms) nor N₂-flux rate predicted responses to nutrient additions. N availability significantly influenced responses of phytoplankton to nutrient additions across years, but this effect was small. The ratio of total N to total P significantly influenced the response to single additions of N and P (these effects were negative and positive, respectively) in summer 2013. Importantly, higher lake primary production and heterocyte count (number of nitrogen fixing cells) were also associated with a stronger, positive response to N + P addition. Overall, these data suggest that planktonic algal assemblages are predominantly characterized by co-limitation by N and P despite large and diverse human impacts on nutrient inputs. Additionally, higher rates of primary production increase the likelihood of co-limitation. Together, these results further support the paradigm shift toward dual management of N and P in aquatic ecosystems.